(untitled) (Conferencea, 2024)
This article describes the pedagogical communication methods used during the lesson, which are important in increasing the effectiveness of the mother tongue education process. It was explained that the improvement of the quality of education is one of the urgent issues of today, as well as the reforms carried out to improve the quality of education in our republic, the decisions and decrees developed by the head of our state. The opinions of research scientists were studied about the role and importance of pedagogical dialogue in improving the quality of education, and the author developed recommendations on the organization of effective dialogue between the teacher and the student.